2013
DOI: 10.3233/nre-130990
|View full text |Cite
|
Sign up to set email alerts
|

Does robot-assisted gait training ameliorate gait abnormalities in multiple sclerosis? A pilot randomized-control trial

Abstract: BACKGROUND: Gait disorders are common in multiple sclerosis (MS) and lead to a progressive reduction of function and quality of life. OBJECTIVE: Test the effects of robot-assisted gait rehabilitation in MS subjects through a pilot randomized-controlled study. METHODS: We enrolled MS subjects with Expanded Disability Status Scale scores within 4.5-6.5. The experimental group received 12 robot-assisted gait training sessions over 6 weeks. The control group received the same amount of conventional physiotherapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 39 publications
2
72
0
Order By: Relevance
“…Other gait parameters, including gait speed, cadence, double support time (DST), and SL, were reported in different studies. Straudi et al (15) and Gandolfi et al (14) also used the GAIT-Rite mat to measure several of the gait parameters noted above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other gait parameters, including gait speed, cadence, double support time (DST), and SL, were reported in different studies. Straudi et al (15) and Gandolfi et al (14) also used the GAIT-Rite mat to measure several of the gait parameters noted above.…”
Section: Resultsmentioning
confidence: 99%
“…Because all of the baseline data included are in balance, we used the raw data directly to compute the pooled MD, which resulted MD = 14.25 (95% CI: 3.19 to 25.32, Z  = 2.53, P  = 0.01, I 2  = 54%), indicating that RAGT is statistically superior to CWT on improving endurance (Figure 3). Four trials (15, 17) also reported follow-up data, so we performed a sensitivity analysis based on the different time points (MD 8.07, 95% CI: −5.48 to 21.61, Z  = 1.17, P  = 0.21, I 2  = 45%). However, there is no significant difference between RAGT and CWT about long-term effect for improving endurance (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…Another study conducted by Straudi et al arrived at a similar result [80] using the Lokomat robotic device with 16 subjects. They conducted a study comparing robot-assisted rehabilitation (8) and conventional walking training (8).…”
Section: Robot-assisted Gait Training and Rehabilitationmentioning
confidence: 55%
“…3b) (Table 3). These findings were in contrast with robot-assisted gait training in which participants had a 7.0 cm/s increase immediately after training but returned to pre levels three months after training [85]. Additionally, spatiotemporal gait parameters at self-selected pace were improved well beyond previous reports employing non-gait specific training methods (legs and trunk resistance training twice a week for eight weeks) [86], supporting that gait quality also improved.…”
Section: Mode Of Training and Clinically Meaningful Recovery Of Gaitmentioning
confidence: 55%
“…We showed that patients with high levels of disability were able to complete GXT in 10 out of 25 occasions (40% success rate) and 50% of our participants achieved 90% of their age-predicted maximal heart rates during GXT, potentially important information needed for planning of future studies among patients with high levels of MS-related disability [26,78,82,84,85,[87][88][89][90][91][92]. We found that our participants with high disability achieved 12.2% greater maximal workload during GXT as a result of training, despite small increases in maximal heart rate (1.8%), maximal respiratory exchange ratio (2.2%), and maximal V O 2 (6.6%).…”
Section: Ability To Perform Gxt and Improvements In Cardiorespiratorymentioning
confidence: 69%